Challenges of implementation of the preventive chemotherapy neglected tropical diseases programme in Ghana. - Desmond Dzidzornu Otoo; Ivy Akushika Agbenu; Mary Adebi Nyamekye; Nana Nimo Appiah-Agyekum (Public Library of Science (PLoS), 2023)
Purpose The Neglected Tropical Diseases programme since its implementation has improved the lives of many in the tropical and sub-tropical areas. Though witnessed many successes, the programme is continually facing challenges thus, preventing the attainment of various objectives. This study seeks to assess the challenges of implementation of the neglected tropical diseases programme in Ghana. Design/methodology/approach The thematic analysis approach was used to analyze qualitative data collected from 18 key public health managers selected through purposive and snowballing procedures from the national, regional and district levels of Ghana Health Service. Data collection was done through in-depth interviews using semi-structured interview guides in line with the objective of the study. Findings The Neglected Tropical Diseases Programme though received funding from external sources, faces multiple challenges which cut across financial, human and capital resources to external control. Specifically, inadequate resources, dwindling volunteerism, poor social mobilization, weak governmental commitment and weak monitoring were major challenges to implementation. These factors work individually and in combination to impede effective implementation. Ensuring state ownership, re-structuring implementation approaches to include top-down and bottom-up approaches and building capacity in monitoring and evaluation are recommended in order to meet the programme objectives and ensure sustainability. Originality This study forms part of an original study on Implementation of the NTDs programme in Ghana. Aside the key issues discussed, it presents first-hand information on major implementation challenges that are relevant to researchers, students, practitioners and the general public and will apply widely to vertically implemented programmes in Ghana.